Comparison of Geoelectric Method with Audio Magnetotelluric Method (ADMT) in Aquifer Position Testing at Udayana University Hospital - Rani Junita Marbun; I Nengah Simpen; I Nengah Sandi; Komang Ngurah Suarbawa; Ni Nyoman Rupiasih; Wayan Gede Suharta (BULETIN FISIKA, 2025)
Groundwater is an important resource for supporting life, including at Udayana University Hospital, which requires a stable supply of clean water. This study aims to compare the Wenner configuration geoelectric method with the Audio Magnetotelluric (ADMT) method in identifying the position of aquifers. Measurements were conducted around the hospital borehole with a track length of 230 m for the geoelectric method and 50 m for the ADMT method. The results showed that with the geoelectric method, the aquifer position was detected at a depth of 30-37 m with a resistivity of 77.5-144 Ωm and with the ADMT method at a depth of 30-38 m with a resistivity of 1-3 Ωm. In terms of time, the ADMT method is superior, with a total time of 50 minutes and the geoelectric method with a total time of 3 hours 20 minutes. From the cost aspect, the geoelectric method is more economical, with a tool cost of around Rp 126,000,000, and the ADMT method with a tool cost of around Rp 205,000,000. The ADMT method is more accurate in detecting the position of aquifers with an accuracy of 96% with a depth range of 100 m, while the accuracy of the geoelectric method is 92% with a depth of 37 m. Based on these results, the ADMT method is recommended for more accurate and efficient groundwater exploration.